School development in challenging social conditions: achieving academic success and management difficulties - Yerdan Sovetovich Katayev; Guzalia Rasikhovna Shagivaleeva; Rsaldy Bagdatovna Orazaliyeva; Liia Nailevna Voronova (Institute of Advanced Engineering and Science, 2026)
The aim of the study is to compare the experiences of working with socially vulnerable children in European countries and the United States with similar needs in the Russian Federation and the Republic of Kazakhstan. The study addresses the problem of social tension negatively affecting children’s academic performance. A qualitative design was combined with elements of quantitative analysis. The study was conducted among fifth- and ninth-grade students (ages 11–12 and 15–16, respectively) in schools in Kazan (Russia) and Almaty (Kazakhstan), involving a total of 255 participants. Academic performance was monitored throughout the school year, with performance changes analyzed using descriptive statistics. The study found that social tension originating from students’ home environments adversely impacts their academic achievement. Data from schools in Kazan and Almaty confirm that educational success depends not only on diligence but also on the ability to solve non-standard tasks. A comparative analysis revealed that pedagogical strategies fostering student self-government and intuitive teaching methods contribute to improved academic performance, even among children from socially disadvantaged groups. The results of the study can be used in university lectures and seminars on pedagogy, as well as for further research on social factors in education.